2017
DOI: 10.1155/2017/9536716
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Quality Characteristics of Wheat Bread Supplemented with Leafy Vegetable Powders

Abstract: The study investigated the effect of supplementation of the leaf powders of Telfairia occidentalis, Amaranthus viridis, and Solanum macrocarpon on the chemical composition and the quality characteristics of wheat bread. The bread samples were supplemented with each of the vegetable leaf powders at 1%, 2%, and 3% during preparation. The bread samples were assayed for proximate composition, mineral composition, physical, sensory, and antioxidant properties using standard methods. The addition of vegetable powder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
51
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 21 publications
15
51
5
Order By: Relevance
“…A positive correlation was observed between the antioxidant capacity as assessed using the FRAP and DPPH· methods and the TPC at days 1 ( r 2 = 0.977 and r 2 = 0.962, respectively) and 7 post‐baking ( r 2 = 0.741 and r 2 = 0.748, respectively). Similar results were reported by Odunlade et al () and Alashi et al () who obtained breads with increased TPC after incorporation of leafy vegetable powders, namely Amaranthus viridis , Solanum macrocarpon , and Telfairia occidentalis , at flour substitution levels ranging from 1% to 3% (w/w). Increased TPC was also observed in breads containing broccoli sprouts (Gawlik‐Dziki et al, ).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…A positive correlation was observed between the antioxidant capacity as assessed using the FRAP and DPPH· methods and the TPC at days 1 ( r 2 = 0.977 and r 2 = 0.962, respectively) and 7 post‐baking ( r 2 = 0.741 and r 2 = 0.748, respectively). Similar results were reported by Odunlade et al () and Alashi et al () who obtained breads with increased TPC after incorporation of leafy vegetable powders, namely Amaranthus viridis , Solanum macrocarpon , and Telfairia occidentalis , at flour substitution levels ranging from 1% to 3% (w/w). Increased TPC was also observed in breads containing broccoli sprouts (Gawlik‐Dziki et al, ).…”
Section: Resultssupporting
confidence: 89%
“…Previous studies observed an increase in the moisture content of breads after inclusion of powdered tomato co‐products into their formulation (Majzoobi, Ghavi, Farahnaky, Jamalian, & Mesbahi, ). In turn, Odunlade et al () observed a decrease in the moisture content of breads containing dried leafy vegetables at flour substitution levels ranging between 1% and 3% (w/w). As expected, a decrease in the moisture content was observed at day 7 because of bread staling ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of various additives to wheat bread formula may influence on its quality attributes, including its yield, volume and sensory evaluation (Karolini‐Skaradzińska et al , ; Odunlade et al , ; Lin & Zhou, ; Prokopov et al , ; Zain et al , ). In the present study, changes in bread yield and volume after formula enrichment with 0.5% and 1.0% OE were insignificant.…”
Section: Resultsmentioning
confidence: 99%